Culturable gut bacteria of Ikan Batak (Neolissochilus sumatranus Weber & de Beaufort, 1916) collected in Toba Samosir, Indonesia - Achmad Dinoto; Rini Handayani; Ninu Setianingrum; Heddy Julistiono (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Dinoto A, Handayani R, Setianingrum N, Julistiono H. 2020. Culturable gut bacteria of Ikan Batak (Neolissochilus sumatranus Weber & de Beaufort, 1916) collected in Toba Samosir, Indonesia. Biodiversitas 21: 4483-4488. Ikan Batak (Neolissochilus sumatranus Weber & de Beaufort, 1916) is one of the fish species that is rarely found in water and have the status of endangered species. In consequence, the loss of endemic fish may contribute to the loss of microorganisms that inhabits the fish as a host. The studies on microorganisms associated with N. sumatranus are very limited. Therefore, the purpose of this study was to isolate and identify the culturable bacteria isolated from the gut of N. sumatranus. Sampling of N. sumatranus was carried out in a river within Toba Samosir area which flows to Lake Toba. Fish gut content was collected for isolating microorganisms using three media, including MRS, 10X diluted MRS, and MRS supplemented with 1% bile salt. Thirteen isolates were successfully isolated and identified based on 16S rRNA. This study revealed various species of gut bacteria recovered from N. sumatranus based on BLAST analysis. The isolates showed closest relationship to species Bacillus subtilis (3 isolates),  Bacillus tequilensis (2 isolates), Tumebacillus ginsengisoli (6 isolates), Klebsiella pneumoniae (1 isolate), and Lactobacillus pentosus (1 isolate) with the similarity ranging at  98.7 to 100%. All 16S rRNA gene nucleotides of isolates have been submitted to GenBank. This study also described the isolates that have a very close relationship with Bacillus tequilla and Bacillus subtilis. Further identification is challenged to obtain a  big picture of the diversity of microorganisms and the functionality in the digestive ecosystem of N. sumatranus for their conservation and bioprospecting of microbial-based aquaculture.